PENGARUH KOMUNIKASI INTERNAL STRES KERJA DAN KONFLIK KERJA TERHADAP KINERJA BERDASARKAN PERSEPSI KARYAWAN PT. ELNUSA PETROFIN CABANG BALIKPAPAN - Nainggolan, Hermin; Agustina, Nanda; Handayani, Lilik; Syam, Shofiana (Jurnal Manajemen dan Bisnis, 2025)
This research aims to determine the influence of internal communication, work stress, and work conflict on performance based on the perceptions employees of PT Elnusa Petrofin Cabang Balikpapan partially and simultaneously. This research data was obtained from employee performance reports for 3 years, namely the 2021-2023 period with a sample size of 41 respondents. The data analysis technique used is with the help of the SPSS version 25 program. Based on the results of the partial hypothesis research test, it shows that the independent variable (internal communication) has no positive and significant effect on (employee performance), a t-count value of -4.437 > from t table 2.026 and a significance value of 0.000 < 0.05. The independent variable (work stress) partially has a negative and insignificant effect on (employee performance). The t value obtained is -0.503 < from t table 2.026 and the significance value is 0.618 < 0.05. The independent variable (work conflict) partially has a negative and insignificant effect on (employee performance). The t value obtained is -0.633 < from t table 2.026 and the significance value is 0.531 > 0.05. Simultaneously, it shows that the variables of internal communication, work stress and work conflict do not have a significant effect on employee performance, obtaining an F value of 0.826 < from F table of 2.85 and a significance value of 0.488 > 0.05